If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+4)+2=-11(x-5)-6
We move all terms to the left:
6(x+4)+2-(-11(x-5)-6)=0
We multiply parentheses
6x-(-11(x-5)-6)+24+2=0
We calculate terms in parentheses: -(-11(x-5)-6), so:We add all the numbers together, and all the variables
-11(x-5)-6
We multiply parentheses
-11x+55-6
We add all the numbers together, and all the variables
-11x+49
Back to the equation:
-(-11x+49)
6x-(-11x+49)+26=0
We get rid of parentheses
6x+11x-49+26=0
We add all the numbers together, and all the variables
17x-23=0
We move all terms containing x to the left, all other terms to the right
17x=23
x=23/17
x=1+6/17
| 2t⋅0=0 | | q-6.95/2=-4.61 | | 2t-32=2t | | 142=h+204 | | 2t=2t-32 | | 360=23x+9.5 | | -8/11+r=1/11 | | 3t-5=4t-19 | | 12/7=0.3/m | | -4y-3+3y=8-2y15 | | 2b+98=2b+34 | | -4t-3+3=3 | | -1.2+u/3=-8.7 | | 17-20x=-4(13+5x) | | 17―20x=-4(13+5x) | | 10x-83=67 | | 10x-83=6 | | u=4u-33 | | 5v-56=v | | 10x+83=67 | | 7p-31=5p-7 | | 5x―9=11 | | 3(b–14)=–12 | | s+95=6s-90 | | 8b+24=5b+91=180 | | 8b+24=5b+91 | | 182*4x=5x+2 | | x+36+3x=180 | | 3/4y=-9/20 | | (x+8)×4=21 | | c=2c-18 | | v=7v-48 |